Electrode materials and processes for their preparation
By employing a binder mixture of aqueous styrene-butadiene rubber and acidic poly(acrylic acid) in lithium-ion battery electrodes, the challenges of high production costs, energy-intensive solvent evaporation, and battery instability are addressed, resulting in improved electrochemical performance and extended battery lifespan.
Patent Information
- Application Number
- JP2022030798
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-12-20
- Filing Date
- 2022-03-01
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2037-06-30
AI Technical Summary
Current electrode materials for lithium-ion batteries face challenges such as high production costs, energy-intensive solvent evaporation, and accelerated chemical degradation due to the use of poly(vinyldifluoride) (PVDF) binders and other polymeric binders that lack flexibility and contribute to battery instability.
The development of an electrode material using a binder mixture comprising an aqueous binder, such as styrene-butadiene rubber (SBR), and an acidic polymer, like poly(acrylic acid) (PAA), which enhances dispersion and ion conductivity, reduces internal resistance, and protects the interface between the current collector and the active material.
This solution improves the electrochemical performance of lithium-ion batteries by enhancing capacity retention, reducing internal resistance, and extending battery lifespan through the use of a more environmentally friendly and cost-effective binder system.
Smart Images

Figure 0007665551000004 
Figure 0007665551000005 
Figure 0007665551000006
Abstract
Description
[Technical field]
[0001] Related Applications This application claims priority to U.S. Provisional Application No. 62 / 356,952, filed June 30, 2016, and U.S. Provisional Application No. 62 / 436,718, filed December 20, 2016, the contents of which are incorporated by reference in their entirety herein for all purposes.
[0002] Technical Field The technical field generally relates to electrode materials and processes for their preparation (e.g., electrode materials using binders and acidic polymers, including acidic polymers or water-soluble binders). The application also relates to the use of the electrode materials for the preparation of electrodes and their use in electrochemical cells (e.g., lithium ion batteries). [Background technology]
[0003] background Polymer binders are widely used in electrochemistry to provide cohesion and adhesion of active materials on the current collector of an electrode. These binders are electrochemically inert and chemically inert. They are also known to contribute significantly to the size and stability of batteries (Yamamoto, H. et al., Lithium-Ion Batteries: Science and Technologies, Springer New York, 2009; pp 163-179, incorporated herein by reference).
[0004] The most commonly used polymer binder is poly(vinyl difluoride) (PVDF). This polymer is usually dissolved in a toxic solvent, i.e., N-methyl-2-pyrrolidone (NMP), which has a very high boiling point (202° C.), before combining it with the active material particles and applying the mixture onto a current collector. ((a) Guerfi, A., J. of Power Sources, 2007, 163 (2), 1047-1052; (b) Lux, SF et al., J. of The Electrochem. Soc., 2010, 157 (3), A320-A325, incorporated herein by reference). Although this polymer is effective as a binder and is electrochemically inert, its industrial use has significant drawbacks, for example, in terms of production costs and costs associated with evaporation of the solvent after coating of the electrode, which requires a significant amount of energy (see Lux et al., supra). Furthermore, battery electrolyte in contact with PVDF induces the formation of lithium fluoride, which accelerates the chemical decomposition of the binder (see Guerfi et al., supra), thus increasing the degradation rate of the battery and accordingly the cell life.
[0005] Another polymer binder used is a mixture of styrene-butadiene rubber (SBR) and methylcellulose (CMC). SBR promotes adhesion on the current collector, while CMC thickens the dispersion and enhances adhesion between active material particles (see Guerfi et al., supra). This mixture is very effective in the case of LiFePO4 and LTO (Chou, SL et al., Phys. Chem. Chem. Phys., 2014, 16(38), 20347-20359, incorporated herein by reference), but is ineffective in LCO (Lee, J.-T. et al., J. of Power Sources, 2007, 173(2), 985-989, incorporated herein by reference). This mixture is also electrochemically inactive and does not contribute positively to the efficiency of the battery.
[0006] Poly(acrylonitrile) (PAN), poly(acrylic acid) (PAA) and poly(vinyl alcohol) (PVA) have also been used in the past as polymer binders for electrodes ((a) Cai, ZP et al., J. of Power Sources, 2009, 189(1), 547-551; (b) Gong, L. et al., Electrochem. Comm., 2013, 29, 45-47; (c) Park, H.-K. et al., Electrochem. Commun., 2011, 13(10), 1051-1053, incorporated herein by reference). However, the lack of flexibility (higher glass transition) of these polymers is a major drawback as electrodes form cracks upon multiple cycles (Tran, B. et al., Electrochim. Acta, 2013, 88, 536-542 (hereby incorporated by reference).
[0007] Thus, the use of polymers that are soluble in environmentally friendly solvents with low boiling points, such as water, is a beneficial improvement for the manufacture of electrodes. Furthermore, it is also desirable for the binder to enhance the dispersion of the active material and contribute to the ionic and / or electronic conductivity of the electrode. For example, increased ionic conductivity can help reduce the internal resistance of the electrode, thus enabling the transport of lithium.
[0008] Furthermore, since the use of activated carbon as a coating on the surface of the active material (Ding, Z. et al., Phys. Chem. Chem. Phys., 2011, 13(33), 15127-15133, incorporated herein by reference), can cause a reaction on the surface of the aluminum current collector (Wan, D. et al., ACS Nano, 2012, 6(10), 9068-9078, incorporated herein by reference), it is also desirable to find a polymeric binder that protects the interface between the current collector and the electrochemically active material in the dispersion. [Prior art documents] [Non-patent literature]
[0009]
Non-licensed literature 1
Non-licensed Document 2
Non-licensed Document 4
Non-licensed Document 5
Non-licensed Document 6
Non-licensed Document 7
Non-licensed literature 9
Non-licensed literature 10
Non-licensed Document 11
[0010] Abstract According to one aspect, the present application relates to an electrode material comprising particles of an electrochemically active material dispersed in a binder, wherein the binder is a mixture comprising an aqueous binder (i.e., a binder soluble in an aqueous solvent) and an acidic polymer, and the aqueous binder is not an acidic polymer. For example, the acidic polymer is selected from poly(acrylic acid) (PAA), poly(methacrylic acid) (PMAA) and combinations thereof, or the acidic polymer is poly(acrylic acid) (PAA). For example, the acidic polymer has an average molecular weight in the range of about 200,000 g / mol to about 600,000 g / mol.
[0011] In one embodiment, the aqueous binder used in the material of the present invention is selected from SBR (styrene butadiene rubber), NBR (butadiene acrylonitrile rubber), HNBR (hydrogenated NBR), CHR (epichlorohydrin rubber), ACM (acrylate rubber), and combinations thereof, for example, the aqueous binder comprises or is SBR. For example, the ratio of aqueous binder:acidic polymer is in the range of about 1:8 to about 8:1, or about 1:5 to about 5:1, or about 1:3 to about 3:1. In one embodiment, the binder further comprises lithium ions derived from a lithium-containing base, such as, for example, lithium hydroxide.
[0012] In one embodiment, the electrochemically active material in the particles comprises a material selected from the group consisting of titanates, lithium titanates, lithium metal phosphates, vanadium oxides, lithium metal oxides, and combinations thereof. For example, the electrochemically active material may be TiO2, Li2TiO3, Li4Ti5O 12 , H2Ti5O 11and H2Ti4O9, or combinations thereof, LiM'PO4 (wherein M' is Fe, Ni, Mn, Co, or combinations thereof), LiV3O8, V2O5, LiMn2O4, LiM''O2 (wherein M'' is Mn, Co, Ni, or combinations thereof), Li(NiM''')O2 (wherein M''' is Mn, Co, Al, Fe, Cr, Ti, or Zr), and combinations thereof. In one embodiment, the electrochemically active material is selected from lithium titanate and lithium metal phosphate, e.g., Li4Ti5O 12 Or LiFePO4.
[0013] In another embodiment, the particle further comprises a carbon coating, e.g., a nanolayer of carbon comprising fibers, on the surface of the particle. In a preferred embodiment, the carbon coating comprises a graphene-type polyaromatic structure incorporating heteroatoms (e.g., oxygen atoms, nitrogen atoms, sulfur atoms, or combinations thereof), e.g., the heteroatoms comprise nitrogen atoms.
[0014] According to another aspect, the present application relates to an electrode material comprising particles of electrochemically active material dispersed in a binder, wherein the binder is an acidic polymer. For example, the acidic polymer is selected from poly(acrylic acid) (PAA), poly(methacrylic acid) (PMAA) and combinations thereof, or the acidic polymer is poly(acrylic acid) (PAA). For example, the acidic polymer has an average molecular weight in the range of about 200,000 g / mol to about 600,000 g / mol. In one embodiment, the particles of active material are as defined herein. In one embodiment, the binder further comprises lithium ions.
[0015] In one embodiment, the electrochemically active material in the particles comprises a material selected from the group consisting of titanates, lithium titanates, lithium metal phosphates, vanadium oxides, lithium metal oxides, and combinations thereof. For example, the electrochemically active material may be TiO2, Li2TiO3, Li4Ti5O 12 , H2Ti5O11 and H2Ti4O9, or combinations thereof, LiM'PO4 (wherein M' is Fe, Ni, Mn, Co, or combinations thereof), LiV3O8, V2O5, LiMn2O4, LiM''O2 (wherein M'' is Mn, Co, Ni, or combinations thereof), Li(NiM''')O2 (wherein M''' is Mn, Co, Al, Fe, Cr, Ti, or Zr), and combinations thereof. In one embodiment, the electrochemically active material is selected from lithium titanate and lithium metal phosphate, e.g., Li4Ti5O 12 or LiFePO4. In one embodiment, the particles further comprise a carbon coating, e.g., a nanolayer of carbon containing fibers, on the surface of the particles. In one example, the carbon coating comprises a graphene-type polyaromatic structure containing heteroatoms (e.g., oxygen, nitrogen, sulfur, or combinations thereof).
[0016] In another aspect, the present technology relates to an electrode material comprising particles of an electrochemically active material dispersed in a polymeric binder, wherein the polymeric binder is a mixture comprising a non-aqueous (non-reactive organic) binder and an acidic polymer. For example, the acidic polymer is selected from poly(acrylic acid) (PAA), poly(methacrylic acid) (PMAA) and combinations thereof, or the acidic polymer is poly(acrylic acid) (PAA). For example, the acidic polymer has an average molecular weight in the range of about 200,000 g / mol to about 600,000 g / mol.
[0017] In one embodiment, the non-aqueous binder is selected from fluorinated binders (e.g., PVDF, PTFE, etc.). For example, the fluorinated binder includes or is PVDF. In one embodiment, the ratio (non-aqueous binder):(acidic polymer) is in the range of about 1:8 to about 8:1, or about 1:5 to about 5:1, or about 1:3 to about 3:1.
[0018] In another embodiment, the electrochemically active material in the particles comprises a material selected from the group consisting of titanates, lithium titanates, lithium metal phosphates, vanadium oxides, lithium metal oxides, and combinations thereof. For example, the electrochemically active material is selected from the group consisting of TiO2, Li2TiO3, Li4Ti5O 12 , H2Ti5O 11 and H2Ti4O9, or combinations thereof, LiM'PO4 (wherein M' is Fe, Ni, Mn, Co, or combinations thereof), LiV3O8, V2O5, LiMn2O4, LiM''O2 (wherein M'' is Mn, Co, Ni, or combinations thereof), Li(NiM''')O2 (wherein M''' is Mn, Co, Al, Fe, Cr, Ti, or Zr), and combinations thereof. In one embodiment, the electrochemically active material is selected from lithium titanate and lithium metal phosphate, e.g., Li4Ti5O 12 or LiFePO4. In one embodiment, the particles further comprise a carbon coating, e.g., a nanolayer of carbon containing fibers, on the surface of the particles. In one example, the carbon coating comprises a graphene-type polyaromatic structure containing heteroatoms (e.g., oxygen, nitrogen, sulfur, or combinations thereof).
[0019] According to another aspect, the present application relates to a process for producing an electrode comprising an electrode material as defined herein, the process comprising the steps of: (a) mixing, in any order, particles of electrochemically active material, the aqueous binder and the acidic polymer in an aqueous solvent to obtain a slurry, (b) casting the slurry of step (a) onto a current collector, and (c) drying the cast slurry to obtain an electrode. In one embodiment, the process further comprises the step of neutralizing the acidic polymer with a lithium-containing base, such as lithium hydroxide, prior to step (a).
[0020] According to a further aspect, the present application relates to a process for producing an electrode comprising an electrode material as defined herein, the process comprising: (a) mixing, in any order, particles of electrochemically active material and the acidic polymer in a solvent to obtain a slurry; (b) casting the slurry of step (a) onto a current collector; and (c) drying the cast slurry to obtain an electrode. In one embodiment, the solvent is an aqueous solvent, e.g., water. The process may further comprise neutralizing the acidic polymer with a lithium-containing base, such as lithium hydroxide, prior to step (a). In another embodiment, the solvent is a non-reactive organic solvent, e.g., NMP, that is compatible with the components of the electrode material. In a further embodiment, the current collector is aluminum or an alloy having aluminum as a main component.
[0021] According to yet another aspect, the present technology relates to a process for producing an electrode comprising the electrode material as defined herein, the process comprising: (a) mixing particles of electrochemically active material, the non-aqueous binder and the acidic polymer in a non-reactive organic solvent in any order to obtain a slurry; (b) casting the slurry of step (a) onto a current collector; and (c) drying the cast slurry to obtain an electrode. In one embodiment, the non-reactive organic solvent is NMP. In a further embodiment, the current collector is aluminum or an alloy having aluminum as a main component.
[0022] The present application also relates to an electrode comprising an electrode material as defined herein on a current collector, or an electrode produced by the process of the present application. Electrochemical cells comprising an electrode, an electrolyte and a counter-electrode as defined herein are also contemplated, as are their uses (e.g., in electric or hybrid automobiles, or ubiquitous IT devices). The present invention provides, for example, the following items. (Item 1) 1. An electrode material comprising particles of an electrochemically active material dispersed in a polymeric binder, wherein the polymeric binder is a mixture comprising an aqueous binder and an acidic polymer. (Item 2) Item 2. The electrode material according to item 1, wherein the acidic polymer is selected from poly(acrylic acid), poly(methacrylic acid), and combinations thereof. (Item 3) 3. The electrode material according to item 2, wherein the acidic polymer is poly(acrylic acid). (Item 4) 4. The electrode material according to any one of items 1 to 3, wherein the acidic polymer has an average molecular weight in the range of about 200,000 g / mol to about 600,000 g / mol. (Item 5) The electrode material according to any one of items 1 to 4, wherein the aqueous binder is selected from SBR (styrene butadiene rubber), NBR (butadiene acrylonitrile rubber), HNBR (hydrogenated NBR), CHR (epichlorohydrin rubber), ACM (acrylate rubber), and combinations thereof. (Item 6) 6. The electrode material according to item 5, wherein the aqueous binder comprises SBR (styrene butadiene rubber). (Item 7) 6. The electrode material according to item 5, wherein the aqueous binder is SBR (styrene butadiene rubber). (Item 8) 8. The electrode material according to any one of items 1 to 7, wherein the ratio (aqueous binder):(acidic polymer) is in the range of about 1:8 to about 8:1, or about 1:5 to about 5:1, or about 1:3 to about 3:1. (Item 9) 9. The electrode material according to any one of items 1 to 8, wherein the binder further contains lithium ions. (Item 10) 10. The electrode material according to any one of items 1 to 9, wherein the electrochemically active material comprises a material selected from the group consisting of titanates, lithium titanates, lithium metal phosphates, vanadium oxides, lithium metal oxides, and combinations thereof. (Item 11) The electrochemically active material is TiO 2 , Li 2 TiO 3 , Li 4 Ti 5 O 12 、H 2 Ti 5 O 11 and H 2 Ti 4 O 9 , or a combination of these, LiM'PO 4 (wherein M' is Fe, Ni, Mn, Co, or a combination thereof), LiV 3 O 8 、V 2 O 5 , LiMn 2 O 4 , LiM''O 2 (where M'' is Mn, Co, Ni, or a combination thereof), Li(NiM''')O 2 Item 11. The electrode material according to item 10, wherein M''' is selected from Mn, Co, Al, Fe, Cr, Ti, or Zr, and combinations thereof. (Item 12) Item 11. The electrode material according to item 10, wherein the electrochemically active material is selected from lithium titanate and lithium metal phosphate. (Item 13) 13. The electrode material according to any one of items 1 to 12, wherein the particles further comprise a carbon coating. (Item 14) Item 14. The electrode material of item 13, wherein the carbon coating is a nanolayer of carbon containing fibers on the surface of the particle. (Item 15) 15. The electrode material according to claim 13 or 14, wherein the carbon coating comprises a graphene-type polyaromatic structure containing heteroatoms. (Item 16) Item 16. The electrode material according to item 15, wherein the heteroatoms are selected from oxygen, nitrogen, sulfur, and combinations thereof. (Item 17) 17. A process for producing an electrode comprising an electrode material as defined in any one of items 1 to 16, the process comprising: a) mixing, in an aqueous solvent, particles of electrochemically active material, the aqueous binder and the acidic polymer in any order to obtain a slurry; b) casting the slurry of step (a) onto a current collector; and c) drying the cast slurry to obtain an electrode; A process that encompasses. (Item 18) Item 18. The process of item 17, further comprising the step of neutralizing the acidic polymer with a lithium-containing base, such as lithium hydroxide, prior to step (a). (Item 19) 19. The process according to item 17 or 18, wherein the current collector is aluminum or an alloy having aluminum as a main component. (Item 20) 1. An electrode material comprising particles of an electrochemically active material dispersed in a binder, wherein the binder is an acidic polymer. (Item 21) 21. The electrode material according to item 20, wherein the acidic polymer is selected from poly(acrylic acid) (PAA), poly(methacrylic acid) (PMAA), and combinations thereof. (Item 22) 21. The electrode material according to item 20, wherein the acidic polymer is poly(acrylic acid) (PAA). (Item 23) 23. The electrode material according to any one of items 20 to 22, wherein the acidic polymer has an average molecular weight in the range of about 200,000 g / mol to about 600,000 g / mol. (Item 24) 24. The electrode material according to any one of items 20 to 23, wherein the binder further contains lithium ions. (Item 25) 25. The electrode material according to any one of items 20 to 24, wherein the electrochemically active material comprises a material selected from the group consisting of titanates, lithium titanates, lithium metal phosphates, vanadium oxides, lithium metal oxides, and combinations thereof. (Item 26) The electrochemically active material is TiO 2 , Li 2 TiO 3 , Li 4 Ti 5 O 12 、H 2 Ti 5 O 11 and H 2 Ti 4 O 9 , or a combination of these, LiM'PO 4 (wherein M' is Fe, Ni, Mn, Co, or a combination thereof), LiV 3 O 8 、V 2 O 5 , LiMn 2 O 4 , LiM''O2 (where M'' is Mn, Co, Ni, or a combination thereof), Li(NiM''')O 2 26. The electrode material according to item 25, wherein M''' is selected from Mn, Co, Al, Fe, Cr, Ti, or Zr, and combinations thereof. (Item 27) 26. The electrode material according to claim 25, wherein the electrochemically active material is selected from lithium titanate and lithium metal phosphate. (Item 28) 28. The electrode material according to any one of items 20 to 27, wherein the particles further comprise a carbon coating. (Item 29) 29. The electrode material of claim 28, wherein the carbon coating is a nanolayer of carbon containing fibers on the surface of the particle. (Item 30) 30. The electrode material according to claim 28 or 29, wherein the carbon coating comprises a graphene-type polyaromatic structure containing heteroatoms. (Item 31) Item 31. The electrode material according to item 30, wherein the heteroatoms are selected from oxygen, nitrogen, sulfur, and combinations thereof. (Item 32) A process for producing an electrode comprising an electrode material as defined in any one of items 20 to 31, the process comprising: a) mixing particles of electrochemically active material and said acidic polymer in a solvent in any order to obtain a slurry; b) casting the slurry of step (a) onto a current collector; and c) drying the cast slurry to obtain an electrode; A process that encompasses. (Item 33) 33. The process according to item 32, wherein the solvent is an aqueous solvent, such as water. (Item 34) 34. The process according to claim 32 or 33, further comprising the step of neutralizing the acidic polymer with a lithium-containing base, such as lithium hydroxide, prior to step (a). (Item 35) 33. The process according to claim 32, wherein the solvent is a non-reactive organic solvent, such as NMP. (Item 36) 36. The process according to any one of items 32 to 35, wherein the current collector is aluminum or an alloy having aluminum as a main component. (Item 37) 1. An electrode material comprising particles of an electrochemically active material dispersed in a polymeric binder, wherein the polymeric binder is a mixture comprising a non-aqueous binder and an acidic polymer. (Item 38) Item 38. The electrode material according to item 37, wherein the acidic polymer is selected from poly(acrylic acid), poly(methacrylic acid), and combinations thereof. (Item 39) Item 39. The electrode material according to item 38, wherein the acidic polymer is poly(acrylic acid). (Item 40) 40. The electrode material according to any one of items 37 to 39, wherein the acidic polymer has an average molecular weight in the range of about 200,000 g / mol to about 600,000 g / mol. (Item 41) 41. The electrode material according to any one of items 37 to 40, wherein the non-aqueous binder is selected from fluorinated binders. (Item 42) Item 42. The electrode material of item 41, wherein the fluorinated binder comprises PVDF. (Item 43) Item 42. The electrode material according to item 41, wherein the fluorinated binder is PVDF. (Item 44) 44. The electrode material according to any one of items 37 to 43, wherein the ratio (non-aqueous binder):(acidic polymer) is within the range of about 1:8 to about 8:1, or about 1:5 to about 5:1, or about 1:3 to about 3:1. (Item 45) 45. The electrode material according to any one of items 37 to 44, wherein the electrochemically active material comprises a material selected from the group consisting of titanates, lithium titanates, lithium metal phosphates, vanadium oxides, lithium metal oxides, and combinations thereof. (Item 46) The electrochemically active material is TiO 2 , Li 2 TiO 3 , Li 4 Ti 5 O 12 、H 2 Ti 5 O 11 and H 2 Ti 4 O 9 , or a combination of these, LiM'PO 4 (wherein M' is Fe, Ni, Mn, Co, or a combination thereof), LiV 3 O 8 、V 2 O 5 , LiMn 2 O 4 , LiM''O 2 (where M'' is Mn, Co, Ni, or a combination thereof), Li(NiM''')O 2 Item 46. The electrode material according to item 45, wherein M''' is selected from Mn, Co, Al, Fe, Cr, Ti, or Zr, and combinations thereof. (Item 47) Item 46. The electrode material according to item 45, wherein the electrochemically active material is selected from lithium titanate and lithium metal phosphate. (Item 48) 48. The electrode material according to any one of items 37 to 47, wherein the particles further comprise a carbon coating. (Item 49) Item 49. The electrode material of item 48, wherein the carbon coating is a nanolayer of carbon containing fibers on the surface of the particle. (Item 50) 50. The electrode material according to claim 48 or 49, wherein the carbon coating comprises a graphene-type polyaromatic structure containing heteroatoms. (Item 51) Item 51. The electrode material according to item 50, wherein the heteroatoms are selected from oxygen, nitrogen, sulfur, and combinations thereof. (Item 52) A process for producing an electrode comprising an electrode material as defined in any one of items 37 to 51, the process comprising: a) mixing, in any order, particles of electrochemically active material, said non-aqueous binder and said acidic polymer in a non-reactive organic solvent to obtain a slurry; b) casting the slurry of step (a) onto a current collector; and c) drying the cast slurry to obtain an electrode; A process that encompasses. (Item 53) 53. The process according to claim 52, wherein the solvent is a non-reactive organic solvent, such as NMP. (Item 54) 54. The process according to claim 52 or 53, wherein the current collector is aluminum or an alloy having aluminum as a main component. (Item 55) 52. An electrode comprising an electrode material as defined in any one of items 1-16, 20-31, and 37-51 on a current collector. (Item 56) 56. The electrode according to claim 55, wherein the current collector is aluminum or an alloy having aluminum as a major component. (Item 57) 55. An electrode produced by the process according to any one of items 17-19, 32-36 and 52-54. (Item 58) 58. An electrochemical cell comprising an electrode, an electrolyte and a counter electrode as defined in any one of items 55 to 57. (Item 59) 59. Use of the electrochemical cell according to item 58 in electric or hybrid vehicles or ubiquitous IT devices.
[0023] Other features and advantages of the present technology will be better understood from the following description taken in conjunction with the accompanying drawings, in which: [Brief description of the drawings]
[0024] [Figure 1] FIG. 1 is a schematic illustration of an embodiment of the present application using an SBR / PAA binder (bottom) compared to using an SBR / CMC binder (top).
[0025] [Diagram 2] FIG. 2 shows the Nyquist plot of an LFP electrode including an SBR / PAA or SBR / PAA-Li binder according to an embodiment of the present application compared to a reference electrode as detailed in Example 2.
[0026] [Diagram 3] Figure 3 shows graphs of the charge (a) and discharge (b) load characteristics of the LFP electrode. The capacity retention was evaluated at various charge and discharge rates (1C, 2C, 4C, and 10C). The results are shown for LFP-SBR / PAA, LFP-SBR / PAA-Li, and LFP-PAA / NMP.
[0027] [Figure 4]Figure 4 shows graphs of the charge (a) and discharge (b) load characteristics of the LTO electrode. The capacity retention was evaluated at various charge and discharge rates (1C, 2C, 4C, and 10C). The results are shown for LTO-PVDF, LTO-PAA / NMP, and LTO-SBR / CMC.
[0028] [Diagram 5] Figure 5 shows graphs of the charge (a) and discharge (b) load characteristics of the LFP-LTO cell. The capacity retention was evaluated at various charge and discharge rates (1C, 2C, 4C and 10C). The results are shown for the reference LFP-PVDF-LTO and LFP-PAA-NMP-LTO cells.
[0029] [Figure 6] Figure 6 shows graphs of the charge (a) and discharge (b) load characteristics of the LFP-LTO cell. The capacity retention was evaluated at various charge and discharge rates (1C, 2C, and 4C). The results are shown for the reference LFP(PVDF)-LTO(PVDF) and LFP(PAA-NMP)-LTO(PVDF) cells. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] Detailed Description The present application relates to a process for the preparation of an electrode material, more particularly an electrode material comprising particles of an electrochemically active material dispersed in a binder comprising an acidic polymeric binder. The present application also relates to a process for the preparation of an electrode material comprising particles of an electrochemically active material dispersed in a binder mixture comprising an aqueous solvent-soluble binder and an acidic polymeric binder, or a binder mixture comprising a non-aqueous solvent-soluble binder and an acidic polymeric binder.
[0031] Examples of acidic polymeric binders include poly(acrylic acid) (PAA), poly(methacrylic acid) (PMAA), or combinations thereof. The slurry to be coated optionally includes additional components, such as inorganic particles, ceramics, salts (e.g., lithium salts), conductive materials, and the like. In one embodiment, no additional carbon source is added to the slurry prior to its coating on the current collector. Examples of binders soluble in aqueous solvents include SBR (styrene butadiene rubber), NBR (butadiene acrylonitrile rubber), HNBR (hydrogenated NBR), CHR (epichlorohydrin rubber), ACM (acrylate rubber), and the like, or any combination of two or more of these. Examples of binders soluble in non-aqueous (non-reactive organic) solvents include ethers, esters, carbonates, nitriles, amides, alcohols, nitromethane, 3-methyl-2-oxazolidinone, N-methyl-2-pyrrolidone (NMP), or mixtures thereof, such as NMP.
[0032] The particles include inorganic particles of electrochemically active materials (e.g., metal oxides and composite oxides) as well as other known active materials. Examples of electrochemically active materials include titanates and lithium titanates (e.g., TiO2, Li2TiO3, Li4Ti5O 12 , H2Ti5O 11 , H2Ti4O9, etc., or combinations thereof), lithium metal phosphates (e.g., LiM'PO4 (where M' is Fe, Ni, Mn, Co, or combinations thereof)), vanadium oxides (e.g., LiVO, VO, etc.), and other lithium and metal oxides (e.g., LiMn2O4, LiMO''O2 (where M'' is Mn, Co, Ni, or combinations thereof), Li(NiMO''')O2 (where M''' is Mn, Co, Al, Fe, Cr, Ti, Zr, etc., or combinations thereof), or combinations thereof. The particles may be freshly formed or obtained from a commercial source and may be microparticles or nanoparticles.
[0033] For example, the particles further include a carbon coating (e.g., a nanolayer of activated carbon). For example, the average thickness of the amorphous carbon layer can be less than 20 nm, or less than 10 nm (e.g., approximately 1.0-1.5 nm). The activated carbon layer can include fibers and / or fused aromatic rings that include carbon atoms and heteroatoms. For example, the activated carbon layer includes graphene oxide or nitrogen-containing graphene-like structures. For example, the coating can include about 4% to about 15% by weight, or about 6% to about 11% by weight, of nitrogen, with the remainder being carbon.
[0034] Also, the surface area of the coated particles, as determined by BET surface area analysis, is approximately 2 m 2 / g to about 20m 2 / g, or about 4m 2 / g to about 15m 2 / g, or about 6m 2 / g to about 10m 2 / g.
[0035] The present application also relates to the preparation of an electrode comprising the electrode material as defined herein. In one example, the electrochemically active particles are mixed with a binder and cast onto a current collector, for example as a slurry in a solvent, which is dried after casting. When the binder is a mixture including a water-soluble binder and an acidic polymer binder, the solvent is an aqueous solvent. On the other hand, when the binder is an acidic polymer binder, the solvent can be an aqueous or non-reactive organic solvent (e.g., NMP). When the binder is a mixture of a non-aqueous binder and an acidic polymer binder, the solvent can be a non-reactive organic non-aqueous solvent (e.g., NMP). The binder is selected with consideration for its compatibility with the electrochemically active material, the current collector, the electrolyte, and other parts of the electrochemical cell that may be in contact with the binder.
[0036] The electrodes produced by the process of the present invention are for use in the assembly of an electrochemical cell further comprising an electrolyte and a counter electrode. The material constituting the counter electrode is selected according to the material used in the electrode. The electrolyte may be a liquid, gel or solid polymer electrolyte and may contain a lithium salt and / or be conductive to lithium ions.
[0037] An example of the present application contemplates the use of PAA (200000-500000 g / mol) in NMP or as a mixture with another binder as defined above (e.g., SBR or PVDF) in proportions adjusted to enhance the dispersion of the active material in water to further increase the electrochemical performance of the electrode. The addition of SBR or PVDF (or related binders) or the use of PAA in NMP has been shown to reduce the glass transition effect and the previously reported fragility of PAA-containing electrodes. Since PAA is an acidic polymer, its acid groups can also be neutralized with a lithium base (e.g., 50 mol%), for example, when the material is prepared in an aqueous solvent, to further reduce the resistance of the binder to lithium ion diffusion in the electrode.
[0038] For example, mixtures of PAA and SBR or PVDF as binders improve the performance of LFP, LTO, LTO activated carbon coatings and activated carbon sources (graphene oxide, carbon doped, etc.). Additionally, mixtures of PAA in NMP as binders have also been shown to improve the performance of LFP and LTO.
[0039] Another example of the present application contemplates the use of an acidic polymer (e.g., PAA (200,000-500,000 g / mol) as the sole binder at a controlled concentration to enhance the dispersion of the active material and / or further increase the electrochemical performance of the electrode. Since PAA is an acidic polymer, its acid groups can also be neutralized with a lithium base (e.g., 50 mol%) to further reduce the resistance of the binder to lithium ion diffusion in the electrode. For example, the concentration of the acidic polymer binder such as PAA in the electrode material can be between about 1 and 8%, e.g., between about 3 and 6%, or between about 4 and 5%.
[0040] Carbon coating materials produced using activated carbon (e.g., nitrogen-containing graphene-type carbon) enhance the performance of LTO anodes. Also, the use of graphene oxide can increase the electronic conductivity of the electrode when compared to carbon powder. However, activated carbon and graphene oxide react with the aluminum current collector to release hydrogen in the presence of water-based binders (e.g., mixtures of SBR and CMC) (see Wan D. et al., supra). Using poly(acrylic acid) (PAA) instead of CMC prevents this contact.
[0041] PAA (or another acidic polymer, such as PMAA) is believed to act as a surfactant because its backbone is hydrophobic and its acid groups are hydrophilic. The polymer self-assembles in the presence of nitrogen-containing activated carbon or graphene oxide coated particles. This finding was further supported by the use of PAA as a polymeric surfactant for the dispersion of various inorganic particles (e.g., Al2O3, TiO2, carbon nanotubes, molybdenum, etc.) (see Loiseau, J. et al., Macromolecules, 2003, 36(9), 3066-3077; Daigle, J.-C. et al., Journal of Nanomaterials, 2008, 8, and Zhong, W. et al., Journal of Polymer Science Part A: Polymer Chemistry, 2012, 50(21), 4403-4407, each of which is incorporated by reference in their entirety for all purposes). PAA acts as a surfactant on the surface, and the acid groups from the polymer stabilize the particle dispersion in water. Samsung has also used low molecular weight PAA to disperse Si- and Sn-based materials (Lee, S. et al., U.S. Patent Application Publication No. 2016 / 0141624, incorporated herein by reference in its entirety for all purposes).
[0042] Thus, the PAA backbone is located close to the current collector, and at the same time, its acidic groups neutralize the basic groups in the carbon source. As a result, the material of the present invention prevented gas generation. Figure 1 shows a schematic diagram of the process. In that particular case, no additional carbon was required. EXAMPLES
[0043] The following non-limiting examples are illustrative embodiments and should not be construed as limiting the scope of the present application. These examples are better understood with reference to the accompanying drawings.
[0044] Example 1: Preparation of C-LTO
[0045] LTO (20 g) was introduced into a 250 mL round bottom flask and stirred by magnetic stirring. 100 mL of nanopure water was then added to the active material in the flask. The resulting slurry was sonicated for 6 minutes at 70% power. After sonication, the slurry was cooled in an ice bath. A solution of 3 g of acrylonitrile and 25 mg of AIBN was added to the flask. The resulting slurry (13% wt of monomer) was sonicated for another 6 minutes at the same power. The slurry was then degassed for 30 minutes using a nitrogen stream. The slurry was then heated to 70° C. for 12 hours with high speed stirring under nitrogen.
[0046] The slurry obtained in the previous step was heated to 180° C. After heating, the slurry was dried by spray drying using the pump at 25% and the blower at 95-100% (percentage of the total power of the equipment).
[0047] The dried particles are then cooled to room temperature for 5°C. -1 The samples were carbonized under air using a temperature gradient from 25°C to 240°C at a rate of 100°C and further held at 240°C for 1 hour. The temperature was then increased to 700°C in 5°C min under an atmosphere of argon:CO2 (75:25) or nitrogen. -1 was increased at a rate of .
[0048] Example 2: Performance at high current for C-LTO / SBR / PAA
[0049] The C-LTO material prepared by the process of Example 1 was mixed with styrene-butadiene rubber (SBR) binder (48% aqueous solution) and CMC (1.5% aqueous solution) or PAA (250000-500000 g / mol) to form a slurry. The solid ratio of C-LTO / SBR / (CMC or PAA) was 96.0 / 2.5 / 1.5 (for 1.0 wt.% dry content of carbon from the coating). The resulting slurry was coated on an aluminum foil with a thickness of 15 microns.
[0050] LFP-LTO coin cells were then assembled with the following configuration: Cell Type: 2032 size coin cell Cathode: LiFePO4(LFP):Carbon black:PVdF=90:5:5 anode: - "Reference": Li4Ti5O 12 (LTO): Carbon black: SBR: CMC = 91:5:2.5:1.5 - "C-LTO 1% CMC": 1% by weight C-Li4Ti5O 12 (LTO):SBR:CMC=96:2.5:1.5 - "C-LTO 1% PAA": 1% by weight C-Li4Ti5O 12 (LTO):SBR:PAA=96:2.5:1.5 Separator: Polyethylene-based, 16μm Electrolyte: 1mol / kg LiPF6PC / DMC / EMC(4 / 3 / 3)
[0051] The cell performance of the three cells obtained was tested and compared. Before the cycle test, the battery was charged and discharged twice at 0.2C at a temperature of 25°C ("xC" is defined as the current that can charge / discharge the full cell capacity in 1 / x hours). Conditions used: Charging: CC-CV (constant current constant voltage) mode Voltage: 2.4V, Current: 0.2C, Cutoff current: 0.03mA Discharge: CC (constant current) mode Cutoff voltage: 0.5V, current: 0.2C
[0052] The effect of PAA on power performance was evaluated by load testing. LFP-LTO coin cells were assembled and cycled (charged and discharged) at 0.2C, 1C, 4C, 10C. After cycling at xC (x=0.2, 1.0, 4.0, 10.0), the battery was cycled to full charge and discharge at 0.2C. For example, 1C is the current that can charge or discharge the full capacity of the cell in 1 hour. 2C is for 30 minutes, 4C is for 15 minutes, and 10C is for 6 minutes.
[0053] For the charging load test, after full discharge at 0.2 C, the LFP-LTO cell was charged at 1 C and then charged again at 0.2 C. Then the cell was discharged at 0.2 C and charged at 2 C.
[0054] For the discharge load test, after full charging at 0.2 C, the LFP-LTO cell was discharged at 1 C and then discharged again at 0.2 C. Then, the cell was charged at 0.2 C and discharged at 2 C.
[0055] Capacity retention was calculated using Equation 1: Capacity retention rate = (Capacity at xC) / (Capacity at 0.2C) x 100 Formula 1
[0056] The capacity in the CC region was used to calculate the charging load characteristics. The results of the load test are shown in Table 1. Conditions used: Charging: CC-CV (constant current constant voltage) mode Voltage: 2.4V, Current: xC, Cutoff current: 0.03mA Discharge: CC (constant current) mode Cutoff voltage: 0.5V, current: xC [Table 1]
[0057] Even though no additional conductive agent (e.g., carbon black) was included in the C-LTO 1% CMC electrode, it showed compatible performance at high currents (e.g., 4C or 10C). However, the C-LTO 1% PAA electrode showed better capacity retention for both charge and discharge compared to the reference at 4C and 10C. The presence of PAA in the binder thus plays a significant role in enhancing the transport of lithium through better coordination.
[0058] Example 3: Resistance properties of LFP / SBR / PAA
[0059] LFP-Li coin cells were then assembled with the following configuration: Cell Type: 2032 size coin cell Cathode: "Reference": LiFePO4 (LFP): Carbon black: PVdF = 90:5:5 "LFP CMC": LFP: Carbon black: SBR: CMC = 91.0: 5.0: 2.5: 1.5 "LFP PAA": LFP: Carbon black: SBR: PAA = 91.0: 5.0: 1.0: 3.0 "LFP PAA-Li": LFP: Carbon black: SBR: PAA-Li = 91.0: 5.0: 1.0: 3.0 Anode: Li metal Electrolyte: 1mol / kg LiPF6PC / DMC / EMC(4 / 3 / 3)
[0060] The first of the three cathodes was prepared as in Example 2, replacing LTO with LFP. LFP PAA-Li was prepared by the following steps:
[0061] PAA (450000 g / mol) was dissolved in water at a concentration of 14.7 wt%. Approximately 50 mol% of the acid groups of the polymer were neutralized with LiOH.H2O. The solution was stirred for 4 h at 80°C and then for 12 h at room temperature to ensure complete dissolution and neutralization of the polymer. LFP-PAA-Li electrodes were then prepared in the same manner as the LFP-PAA electrodes, using PAA-Li instead of PAA.
[0062] Before the cycle test, the battery was charged and discharged twice at 0.2C and 25°C: Charging: CC-CV (constant current constant voltage) mode Voltage: 3.8V, Current: 0.2C, Cutoff current: 0.03mA Discharge: CC (constant current) mode Cutoff voltage: 2.0V, current: 0.2C
[0063] Electrochemical impedance spectroscopy (EIS) was performed using the above LFP-Li coin cell at state of charge (SOC) = 50% and compared with other cells (frequency: 1 MHz to 10 mHz, AC amplitude: 10 mV).
[0064] Figure 2 shows the Nyquist plots of the different cells. When using CMC, the resistance is reduced compared to the reference cell. On the other hand, replacing CMC with PAA showed a reduction in the reaction resistance compared to CMC. The use of PAA-Li showed further improved results, where the reaction resistance was less than half of that obtained with the reference. The addition of lithium ions in the binder further improves the transport of lithium through the creation of lithium channels in the PAA matrix.
[0065] Example 4: Effect of PAA on Capacity, Efficiency and Capacity Retention of LFP and LTO Cells
[0066] Electrodes were prepared as in Examples 2 and 3, substituting NMP for water when PVDF was used. If the composition of the electrode is not given in Examples 2 or 3, the composition is as follows: Cathode: "LFP PAA-NMP" (Figure 3): LFP: carbon black: PAA = 91.0: 5.0: 4.0 (prepared in NMP) "LFP PAA-NMP" (Figure 6): LFP: carbon black: PAA = 90.0: 5.0: 5.0 (prepared in NMP) anode: "LTO PVDF": LTO: Carbon black: PVDF = 90:5:5 "LTO PAA-NMP" (Figure 4): LFP: carbon black: PAA = 91.0: 5.0: 4.0 (prepared in NMP) "LTO PAA-NMP" (Figure 6): LFP: carbon black: PAA = 90.0: 5.0: 5.0 (prepared in NMP)
[0067] FIG. 3 highlights the charge (a) and discharge (b) load characteristics of the LFP electrode. The capacity retention was evaluated at various charge and discharge rates (1C, 2C, 4C, and 10C). The graph compares the capacity retention (%) of LFP-SBR / PAA, LFP-SBR / PAA-Li, and LFP-PAA-NMP. The solid ratio used in FIG. 3 is “LFP The ratio of PAA-NMP:LFP:carbon black:PAA was 91.0:5.0:4.0.
[0068] Table 2 shows the charge and discharge efficiencies of the LFP-SBR / PAA, LFP-SBR / PAA-Li and LFP-PAA-NMP blends at 0.3 mA, if any. The nominal charge / discharge efficiency % at 0.01V and 0.6mA is shown. [Table 2]
[0069] The charge (a) and discharge (b) load characteristics of the LTO electrode are shown in FIG. 4. The capacity retention was evaluated at various charge and discharge rates (1C, 2C, 4C and 10C). The graph compares the results of LTO-PVDF or LTO-PAA / NMP and LTO-SBR / CMC. A clear improvement in capacity retention is noticeable at high charge and discharge rates (10C) for the PAA electrode in comparison with LTO-PVDF and LTO-SBR / CMC. The solid ratio used in FIG. 4 was "LTO PAA-NMP":LFP:carbon black:PAA=91.0:5.0:4.0.
[0070] Table 3 contains the formula charge / discharge efficiency % at 0.25 mA and the nominal charge / discharge efficiency % at 0.5 mA for the LTO-PVDF reference, LTO-PAA / NMP and LTO-SBR / CMC. [Table 3]
[0071] The charge (a) and discharge (b) load characteristics of the LFP-LTO cell are shown in FIG. 5. The capacity retention was evaluated at various charge and discharge rates (1C, 2C, 4C and 10C). FIG. 5 highlights the results of the LFP-PVDF-LTO reference in comparison to the LFP-PAA / NMP-LTO cell. Again, a significant improvement in capacity retention at high rates of charge and discharge (4C and 10C) can be observed for the LFP-PAA / NMP-LTO cell in comparison to the reference.
[0072] Graphs of the charge (a) and discharge (b) load characteristics of the LFP-LTO cells are shown in FIG. 6. The capacity retention was evaluated at various charge and discharge rates (1C, 2C, and 4C). The results are shown for the LFP(PVDF)-LTO(PVDF) reference and LFP(PAA-NMP)-LTO(PVDF) cells. Once again, a significant improvement in capacity retention at high charge and discharge rates (4C) can be observed for the PAA-containing cells in comparison to the PVDF reference. Thus, it is shown that the presence of PAA in the binder plays a significant role in enhancing lithium transport. The LFP-LTO had the following composition: "LFP PAA-NMP": LFP: carbon black: PAA = 90.0: 5.0: 5.0 "LTO PAA-NMP": LFP: Carbon black: PAA = 90.0: 5.0: 5.0
[0073] Many modifications can be made to any of the above described embodiments without departing from the scope of the present invention. Any references, patents or scientific literature documents referred to in this application are incorporated by reference herein in their entirety for all purposes.
Claims
1. 1. An electrode material comprising particles of an electrochemically active material dispersed in a polymer binder, the particles comprising a carbon coating comprising graphene oxide or nitrogen-containing activated carbon, and the polymer binder is an acidic polymer selected from poly(acrylic acid), poly(methacrylic acid), and combinations thereof.
2. The electrode material of claim 1 , wherein the acidic polymer is poly(methacrylic acid).
3. The electrode material of claim 1 , wherein the acidic polymer is poly(acrylic acid).
4. The electrode material according to any one of claims 1 to 3, wherein the acidic polymer further comprises lithium ions.
5. 5. The electrode material of claim 1, wherein the electrochemically active material comprises a material selected from the group consisting of titanates, lithium titanates, lithium metal phosphates, vanadium oxides, lithium metal oxides, and combinations thereof.
6. The electrochemically active material is TiO 2 , Li 2 TiO 3 , Li 4 Ti 5 O 12 , H 2 Ti 5 O 11 and H 2 Ti 4 O 9 , or a combination thereof, LiM'PO 4 (wherein M' is Fe, Ni, Mn, Co, or a combination thereof), LiV 3 O 8 , V 2 O 5 , LiMn 2 O 4 , LiM''O 2 (wherein M″ is Mn, Co, Ni, or a combination thereof), Li(NiM′″)O 2 6. The electrode material of claim 5, wherein M''' is selected from Mn, Co, Al, Fe, Cr, Ti, or Zr, and combinations thereof.
7. 6. The electrode material of claim 5, wherein the electrochemically active material is selected from lithium titanate and lithium metal phosphate.
8. 8. The electrode material according to any one of claims 1 to 7, wherein the carbon coating is a nanolayer of carbon comprising fibres on the surface of the particle.
9. The electrode material according to any one of claims 1 to 8, wherein the carbon coating comprises nitrogen-containing activated carbon, the nitrogen-containing activated carbon having a graphene-type polycyclic aromatic structure.
10. 10. The electrode material of claim 9, wherein the nitrogen-containing activated carbon comprises oxygen heteroatoms, sulfur heteroatoms, and combinations thereof.
11. A process for producing an electrode comprising an electrode material according to any one of claims 1 to 10, the process comprising the steps of: a) mixing particles of electrochemically active material and the acidic polymer in any order in a solvent to obtain a slurry; b) casting the slurry of step (a) onto a current collector; c) drying the cast slurry to obtain an electrode; The process includes:
12. The process of claim 11 , wherein the solvent is an aqueous solvent.
13. The process of claim 12, wherein the aqueous solvent is water.
14. The process of any one of claims 11 to 13, further comprising the step of neutralizing the acidic polymer with a lithium-containing base prior to step (a).
15. 15. The process of claim 14, wherein the lithium-containing base is lithium hydroxide.
16. 16. The process of claim 15, wherein the solvent is a non-reactive organic solvent.
17. 17. The process of claim 16, wherein the non-reactive organic solvent is N-methyl-2-pyrrolidone.
18. The process of any one of claims 11 to 17, wherein the current collector is aluminum or an alloy having aluminum as a main component.
19. 1. An electrode material comprising particles of an electrochemically active material dispersed in a polymeric binder, the particles comprising a carbon coating comprising graphene oxide or nitrogen-containing activated carbon, the polymeric binder being a mixture of a non-aqueous binder and an acidic polymer selected from poly(acrylic acid), poly(methacrylic acid), and combinations thereof.
20. 20. The electrode material of claim 19, wherein the acidic polymer is poly(methacrylic acid).
21. 20. The electrode material of claim 19, wherein the acidic polymer is poly(acrylic acid).
22. 22. The electrode material according to any one of claims 19 to 21, wherein the non-aqueous binder is selected from fluorinated binders.
23. 23. The electrode material of claim 22, wherein the fluorinated binder comprises poly(vinyl difluoride).
24. 23. The electrode material of claim 22, wherein the fluorinated binder is poly(vinyl difluoride).
25. 25. The electrode material according to any one of claims 19 to 24, wherein the weight ratio of (non-aqueous binder):(acidic polymer) is in the range of 1:8 to 8:1, or 1:5 to 5:1, or 1:3 to 3:
1.
26. 26. The electrode material of any one of claims 19 to 25, wherein the electrochemically active material comprises a material selected from the group consisting of titanates, lithium titanates, lithium metal phosphates, vanadium oxides, lithium metal oxides, and combinations thereof.
27. The electrochemically active material is TiO 2 , Li 2 TiO 3 , Li 4 Ti 5 O 12 , H 2 Ti 5 O 11 and H 2 Ti 4 O 9 , or a combination thereof, LiM'PO 4 (wherein M' is Fe, Ni, Mn, Co, or a combination thereof), LiV 3 O 8 , V 2 O 5 , LiMn 2 O 4 , LiM''O 2 (wherein M″ is Mn, Co, Ni, or a combination thereof), Li(NiM′″)O 2 27. The electrode material of claim 26, wherein M''' is selected from Mn, Co, Al, Fe, Cr, Ti, or Zr, and combinations thereof.
28. 28. The electrode material of claim 27, wherein the electrochemically active material is selected from lithium titanate and lithium metal phosphate.
29. Electrode material according to any one of claims 19 to 28, wherein the carbon coating is a nanolayer of carbon comprising fibres on the surface of the particle.
30. 30. The electrode material according to any one of claims 19 to 29, wherein the carbon coating comprises nitrogen-containing activated carbon, the nitrogen-containing activated carbon having a graphene-type polyaromatic structure.
31. 31. The electrode material of claim 30, wherein the nitrogen-containing activated carbon comprises oxygen heteroatoms, sulfur heteroatoms, and combinations thereof.
32. A process for producing an electrode comprising an electrode material according to any one of claims 19 to 31, the process comprising the steps of: a) mixing, in any order, particles of electrochemically active material, said non-aqueous binder, and said acidic polymer in a non-reactive organic solvent to obtain a slurry; b) casting the slurry of step (a) onto a current collector; c) drying the cast slurry to obtain an electrode; The process includes:
33. 33. The process of claim 32, wherein the solvent is a non-reactive organic solvent.
34. 34. The process of claim 33, wherein the non-reactive organic solvent is N-methyl-2-pyrrolidone.
35. The process of any one of claims 32 to 34, wherein the current collector is aluminum or an alloy having aluminum as a major component.
36. 32. An electrode comprising the electrode material according to any one of claims 1 to 10 and 19 to 31 on a current collector.
37. 37. The electrode of claim 36, wherein the current collector is aluminum or an alloy having aluminum as a major component.
38. 38. An electrochemical cell comprising an electrode according to claim 36 or 37, an electrolyte, and a counter-electrode.
39. 40. Use of the electrochemical cell of claim 38 in an electric or hybrid vehicle, or in a ubiquitous IT device.
Citation Information
Patent Citations
Preparation method of lithium ion battery electrode active material
CN103515589A
Composite electrode active material, electrode and lithium battery containing the composite electrode active material, and method of preparing the composite electrode active material
EP2645455A1
Negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
JP2013229163A
Method for manufacturing negative electrode for lithium ion secondary battery, and method for manufacturing lithium ion secondary battery
JP2016062706A
Binder composition for secondary batteries, slurry composition for secondary batteries, negative electrode for secondary batteries, and secondary battery
WO2014141721A1